The Effect of the Peer Tutoring Method in Online English Grammar Learning among Health Science Students - Atur Semartini (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
The peer tutoring method is a student-centered learning approach. This method offers numerous benefits not only in terms of students’ academic performance but also in their personal development. While the peer tutoring method has been widely implemented across various classroom settings, research exploring its effect in online English grammar learning, particularly among health science students, remains limited. This study aims to investigate the effect of implementing peer tutoring in online English grammar learning for health science students. A mixed-methods approach, combining both quantitative and qualitative methods, was employed in this study. A total of 58 health science students participated. The quantitative method involved distributing pre-tests and post-tests, with the resulting data was analyzed to assess the effect of peer tutoring. The qualitative method consisted of distributing questionnaires to obtain students’ perceptions of the peer teaching implementation. The questionnaires included both open and closed questions. The findings revealed a statistically significant improvement in students’ performance, as indicated by an increase in average pre-test and post-test scores (p < 0.05). Additionally, the questionnaire responses indicated that students felt more motivated to engage in learning, as the class became more engaging and the material easier to comprehend through the peer tutoring method. Another reported benefit was that students felt more confident to ask and answer questions when peer tutoring was employed. In conclusion, the implementation of the peer tutoring method in online English grammar learning enhanced students’ comprehension, motivation, and self-confidence in classroom interactions.